T cell immunoengineering with advanced biomaterials - Delcassian, Derfogail; Sattler, Susanne; Dunlop, Iain E. (Royal Society of Chemistry, 2017)
Recent advances in biomaterials design offer the potential to actively control immune cell activation and behaviour. Many human diseases, such as infections, cancer, and autoimmune disorders, are partly mediated by inappropriate or insufficient activation of the immune system. T cells play a central role in the host immune response to these diseases, and so constitute a promising cell type for manipulation. In vivo, T cells are stimulated by antigen presenting cells (APC), therefore to design immunoengineering biomaterials that control T cell behaviour, artificial interfaces that mimic the natural APC-T cell interaction are required. This review draws together research in the design and fabrication of such biomaterial interfaces, and highlights efforts to elucidate key parameters in T cell activation, such as substrate mechanical properties and spatial organization of receptors, illustrating how they can be manipulated by bioengineering approaches to alter T cell function.